The Effect of Return on Equity, Earning Per Share, and Net Profit Margin on Stock Prices of Banking Companies Listed on the Indonesia Stock Exchange for the Period of 2018 – 2020 - Edi Wibowo; Setyaningsih Sri Utami; Alung Rufti Asmoro Dewati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the significance of the effect of return on equity (ROE), earnings per share (EPS), and net profit margin (NPM) on the stock prices of banking companies listed on the Indonesia Stock Exchange for the period 2018 - 2020. Sources of data used are secondary data. The research sample is 23 banking companies with purposive sampling technique. Data collection techniques using the method of documentation. The data analysis technique used in this research is the classical assumption test, multiple linear regression test, t test (partial), F test (simultaneous) and the coefficient of determination test. The results of this study concluded that return on equity (ROE) has no significant effect on stock prices. Earning per share (EPS) has no significant effect on stock prices. Net profit margin (NPM) has a significant effect on stock prices. Meanwhile, return on equity (ROE), earnings per share (EPS), and net profit margin (NPM) simultaneously have a significant effect on the stock prices of banking companies listed on the Indonesia Stock Exchange for the period 2018 - 2020.